Beyond Expectations: Corporate Governance's Insufficiency in Fraud Prevention - Nuraini A, Nuraini A; Ariani, Nita Erika; Lautania, Maya Febrianty (Journal of Accounting Research, Organization and Economics, 2024)
Objective The specific objectives to be achieved in this research are to (1) test the Beneish model (1999) as a predictor of reliable manipulation or indicator to reveal signals or symptoms of financial reporting fraud. (2) Test whether corporate governance effectiveness reduces financial statement fraud.Design/Methodology The research analyzed publicly listed non-financial firms listed in Indonesia's stock exchange (IDX) from 2017 to 2022. Simple random sampling was used to select 86 companies per year, resulting in 617 year-firm observations. Data analysis was carried out by logistic regression multiple with panel data. The test was carried out by adopting the Beneish benchmark index (Z-score) model which is effective for predicting indications of fraudulent financial statements.Results The test results show that there is 99.8% of incidents indicated financial statement fraud and the other 0.2% did not indicate financial statement fraud. Corporate governance mechanisms consisting of institutional ownership, audit committees, and audit quality does not mitigate fraud. It is anticipated that the research's contribution will serve as a practical guide and reference for the examination of indicators of fraud in corporate finances. The findings of this study are expected to provide valuable insights for policymakers and regulators seeking to improve corporate governance practices.Research limitations/implications This research does not incorporate the competency and capability specifications of governance structures such as the board of commissioners, audit committees, and external auditors. Future investigations are anticipated to delve more profoundly into the internal and external corporate governance capabilities and specifications.Novelty/Originality This study reveals that, on the whole, a significant proportion of companies are implicated in fraudulent activities, while corporate governance mechanisms are deemed inadequate in overseeing management activities conducive to fraud. The outcomes of this research challenge the prevailing paradigm of corporate governance as an effective deterrent against fraudulent behavior.